The answer is
[tex]\frac{-6i-3}{5}[/tex].
Before we rationalize the denominator, we must simplify the numerator and denominator. We evaluate the square root on the top, and combine like terms on the bottom:
[tex]\frac{\sqrt{-9}}{(4-7i)-(6-6i)}
\\
\\=\frac{\sqrt{9i^2}}{4-6-7i--6i}
\\
\\=\frac{3i}{-2-i}[/tex]
To rationalize the denominator, we multiply by the conjugate. The conjugate is found by making the imaginary term of the complex number, the i part, the opposite sign. The conjugate of -2-i is -2+i:
[tex]\frac{3i}{-2-i}\times \frac{-2+i}{-2+i}
\\
\\=\frac{3i(-2+i)}{(-2-i)(-2+i)}
\\
\\=\frac{3i\times -2 + 3i\times i}{-2\times -2 + -2\times i + -2\times -i + -i\times i}
\\
\\=\frac{-6i+3i^2}{4-2i+2i-i^2}
\\
\\=\frac{-6i+3(-1)}{4-i^2}=\frac{-6i-3}{4-(-1)}=\frac{-6i-3}{5}[/tex]